Professional and Personal Identity, Precarity and Discrimination in Global Arts Journalism. (26th October 2022) - Sharp, Rob; Vodanovic, Lucia
ABSTRACT: Arts journalism, journalism on the arts and entertainment industries, has been primarily defined in a Western European context within Journalism Studies. Yet this neglects the globalised nature of arts and entertainment production and consumption and the mobile reporters who cover it, and the nationally contingent challenges and opportunities they face. In a world still grappling with the Covid-19 pandemic, arts reporters face a triple threat: the precarity of what is often a freelance career, the financial disruption of the global media and entertainment industries, and the biases of a media ecosystem that favours reporters from the Global North. Drawing on 24 interviews with arts journalists from 12 different countries in four continents in 2020–2021, we explore how such journalists are increasingly subsidising their work with employment beyond the media sector. Arts journalists from Europe grapple with complex issues relating to their professional and personal identities, in contrast to journalists from the Global South, where questions relate primarily to economic and structural challenges. Journalists from West Africa interviewed face increasing if sporadic interest from media organisations in global economic centres, and the emerging content possibilities of internationally funded digital and streaming platforms, mirroring broader economic flows of capital and labour.